Dual-network CO2 response type gel particle and application thereof

By introducing zwitterionic monomers and CO2-responsive monomers into CO2-responsive gel particles, a dual network structure is formed, and metal ions and coordination water are used to form metal coordination bonds, the problem of the reduction of strength of existing gel particles in water with high mineralization is solved, and efficient micro-crack sealing and strength maintenance are achieved.

CN119529180AActive Publication Date: 2025-02-28CHINA UNIV OF PETROLEUM (EAST CHINA) +1

Patent Information

Application Number
CN202510096453.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-02-28
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

The existing CO2-responsive gel particles have low efficiency in sealing micro-cracks with high mineralization during CO2 flooding, and are susceptible to physical damage under high pressure conditions, resulting in reduced strength.

Method used

By introducing zwitterionic monomers and two CO2-responsive monomers on the basis of acrylamide monomers, a dual network structure is formed, and metal ions and coordination water in mineralized water are used to form metal coordination bonds to enhance the strength and water retention properties of gel particles.

Benefits of technology

The CO2-responsive gel particles that maintain high strength in high mineralization water are achieved, which significantly enhances its ability to seal micro-cracks during CO2 driving and avoids the reduction of strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The invention relates to the technical field of oil and gas field development, in particular to a double-network CO2 response type gel particle and application thereof.The first-layer network is formed by covalent bonds between acrylamide, zwitterions and CO2 response monomers (composed of vinylpyridine and DMAEMA) in the gel particle and a cross-linking agent, and the first-layer network is formed by covalent bonds between Ca < 2 + > in mineralized water, pyridine, SO3 <-> in the zwitterionic monomers and coordinated water; coordination bonds exist among Mg < 2 + >, pyridine, carboxyl (acylamino is partially hydrolyzed) and coordinated water, a second-layer network is formed under the synergistic effect of pi-pi bonds among aromatic rings, and the strength of the gel is enhanced through the toughness of the double-network structure. Due to the introduction of an aromatic ring sulphobetaine monomer and water molecules carried by coordinate bonds, the strength of the gel particles in mineralization water is increased, and meanwhile, the gel particles show higher water-retaining property. Due to the introduction of CO2 response monomers with different pKa values, the particles have good CO2 responsiveness, and still have the dual-network structure in mineralized water after response.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas field development, in particular to a double-network CO2 responsive gel particle and application thereof. Background Art

[0002] CO2 flooding can achieve a win-win situation of improving oil reservoir recovery and storing CO2. Although this technology has been widely developed and applied, the existence of natural fractures in the formation causes gas channeling during CO2 flooding, which reduces the sweep efficiency of CO2. Pre-crosslinked gel particles (PPG) are widely used in the process of gas channeling control due to their good sealing performance for fractured reservoirs.

[0003] Conventional gel particles are generally synthesized from acrylamide as a monomer, and cross-linked with organic or inorganic cross-linking agents. This makes conventional polymer gel particles face two major problems when plugging micro-fractures in formations with high mineralization, especially divalent metal ion content, during CO2 flooding. On the one hand, cations in formation water will shield the negatively charged groups in the polymer, weaken the interaction between polymer molecules, reduce the elastic free energy of the system, make it easier to reach a stable state, and reduce the water absorption capacity of the particles. In order to overcome this shortcoming of conventional polymer gel particles, zwitterionic monomers or cationic monomers are introduced during the polymer preparation process to form polyampholytes, which can show the "reverse polyelectrolyte effect" of volume swelling in salt solutions. However, these gels show a typical swelling-weakening phenomenon due to the dilution of the network, and the mechanical strength decreases after swelling. On the other hand, the decrease in pH during CO2 flooding destroys the cross-linking structure of conventional polymer gel particles, resulting in dehydration and gel breaking, so CO2-responsive gel particles have attracted people's attention.These gel particles generally contain cationic groups such as dimethyldiallylammonium chloride (Bobo Zhou, Wanli Kang, HongbinYang, Tongyu Zhu, Hongwen Zhang, Xinxin Li, BauyrzhanSarsenbekuly,TurtabayevSarsenbek. Preparation and properties of an acid-resistantpreformed particle gel for conformance control[J]. Journal of PetroleumScience and Engineering,197,2021,107964.) or organic amine monomers with CO2 responsiveness, such as N,N-dimethylaminoethyl methacrylate (DMAEMA) (Liu Yajie. Preparation and performance enhancement of CO2 responsive gels[D]. China University of Petroleum (Beijing), 2023.), vinylimidazole (Chen Wuhua, Liu Zhicong, Wang Yefei, Ding Mingchen, Cui Shizhang. A CO2 responsive salt-resistant polymer gel particle and its application[P], 2024.), dimethylaminopropylmethacrylamide (DMAPMA) (Meng Mu, Hongyao Yin, YujunFeng. CO2-responsive polyacrylamide microspheres with interpenetrating networks[J]. Journal of Colloid and Interface Science, 497, 2017, 249.), etc., which significantly increases its expansion multiple in an acidic environment. However, a significant increase in the expansion multiple often leads to a decrease in gel strength. In particular, the increase in mineralization in formation water will reduce the pH value of the system (Reza K. Haghi, Antonin Chapoy, Luís MC Peirera, Jinhai Yang, Bahman Tohidi. pH of CO2saturated water and CO2saturated brines: experimental measurements and modeling[J]. International Journal of Greenhouse Gas Control, 66, 2017, 190.), further damaging the strength of the gel.

[0004] The obvious reduction in expansion multiple or strength limits the use of gel particles in the formation, especially when exposed to high pressure conditions in the formation, the reduction in strength makes the gel particles susceptible to physical damage, thereby reducing their plugging efficiency. Therefore, how to prepare a CO2-responsive gel particle that is swelled and strengthened in mineralized water and can maintain a high strength in mineralized water after response is of great significance for CO2 flooding in highly mineralized micro-fracture reservoirs. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a double-network CO2 responsive gel particle and its application. On the basis of acrylamide monomer, zwitterionic monomers and two CO2 responsive monomers are introduced. Through the interaction between the monomers and with divalent metal ions in formation water, the gel particles can achieve the characteristics of swelling enhancement in mineralized water, good CO2 response effect and still have high strength in highly mineralized water after response.

[0006] In order to achieve the above technical effects, the present invention uses the following technical solutions: A double-network CO2-responsive gel particle is prepared by the following method: S1. Add acrylamide, zwitterionic monomer, CO2 responsive monomer and emulsifier into deionized water, stir and mix to obtain a first mixed solution; S2. The pH of the first mixed solution was adjusted to 7, and N2 was introduced into the first mixed solution under an ice bath to exhaust the air to obtain a second mixed solution; S3. The initiator and the cross-linking agent were successively added to the second mixed solution under stirring, the temperature was adjusted to 30 ℃ -60 ℃ and kept passing N2, and the reaction was carried out for 2h-4h to obtain a reaction product; S4. The reaction product obtained in step S3 is washed with anhydrous ethanol, dried, ground and sieved to obtain the target product, double-network CO2-responsive gel particles; In the preparation method, the percentage of each component is: 15%-20% acrylamide, 5-10% zwitterionic monomer, 5-10% CO2 responsive monomer, 0.25-1% emulsifier, 0.05%-0.25% crosslinker, 0.075%-0.15% initiator and the balance water. The CO2 responsive monomer is composed of vinyl pyridine and N,N-dimethylaminoethyl methacrylate (DMAEMA) in a mass ratio of (0.5-1):1.

[0007] Preferably, in step S1, deionized water is used.

[0008] Preferably, the zwitterionic monomer is selected from 4-(2-sulfoethyl)-1-(4-vinylbenzyl)pyridinium betaine, 3-(1-(4-vinylbenzyl)-1H-imidazol-3-ium)propane-1-sulfonate or 3-(dimethyl(4-vinylbenzyl)amino)propanesulfonate.

[0009] Preferably, the vinyl pyridine is selected from one of 4-vinyl pyridine and 2-vinyl pyridine; further preferably, the mass ratio of vinyl pyridine to DMAEMA is 2:3; more preferably, the vinyl pyridine is selected from 4-vinyl pyridine.

[0010] Preferably, the emulsifier is one or two of sodium dodecyl sulfate, OP-10, and sodium stearate. More preferably, the emulsifier is a mixture of sodium dodecyl sulfate and OP-10 in a mass ratio of 1:4.

[0011] Preferably, the crosslinking agent is selected from one of N,N'-methylenebisacrylamide and polyethylene glycol diacrylate or a mixture of the two. More preferably, when the crosslinking agent is selected from N,N'-methylenebisacrylamide and polyethylene glycol diacrylate, the mass ratio of the two is (1.5-6):1; further preferably, the mass ratio is 4:1.

[0012] More preferably, the cross-linking agent is N,N′-methylenebisacrylamide.

[0013] Preferably, the initiator is an azo compound 2,2′-azo[2-(2-imidazolin-2-yl)propane] dihydrochloride or the initiator is composed of sodium bisulfite and ammonium persulfate; further preferably, when the initiator is composed of sodium bisulfite and ammonium persulfate, the molar ratio of sodium bisulfite to ammonium persulfate is in the range of (0.6-1.2):1.

[0014] Preferably, in step S2, the ice bath temperature is 0°C.

[0015] Preferably, in step S3, the stirring speed is 100 rpm-500 rpm; further preferably, the stirring speed is 200 rpm.

[0016] Preferably, in step S4, the drying temperature is 60° C., the drying time is 48 h, and the particles with an initial particle size of less than 135 μm are screened using a sieve.

[0017] Preferably, in the preparation method, the mass percentage of each component is: 15% acrylamide, 10% zwitterionic monomer, 10% CO2 responsive monomer, 0.3% emulsifier, 0.1% cross-linking agent, 0.1% initiator and balance water, wherein the CO2 responsive monomer is composed of 4-vinylpyridine and DMAEMA in a mass ratio of 2:3.

[0018] The double-network CO2-responsive gel particles provided by the present invention have a first layer of three-dimensional network structure formed by covalent bonds among acrylamide, zwitterionic monomers, CO2-responsive monomers and crosslinking agents in the gel particles, and the Ca2+-responsive gel particles in the mineralized water are degraded. 2+ SO3 in ionic, pyridyl, zwitterionic monomers - and between coordinated water, and, Mg in mineralized water 2+ There are metal coordination bonds between ions, pyridine groups, carboxyl groups (produced by partial hydrolysis of amide groups) and coordinated water, and the π-π stacking effect between the aromatic rings forms a second-layer network structure. The toughness of the double network structure significantly enhances the strength of the gel; the introduction of aromatic ring sulfobetaine zwitterionic monomers with "anti-polyelectrolyte effect" and a large number of water molecules carried by the metal coordination bonds increase the strength of the gel particles in highly mineralized water while showing stronger water retention. CO2-responsive monomers vinylpyridine and DMAEMA with different pKa values ​​are introduced into the gel particles at the same time. When CO2 flooding is carried out in fractured reservoirs, DMAEMA with a high pKa value is protonated first, which significantly increases the expansion multiple of the gel particles, while vinylpyridine with a low pKa value can still react with Ca due to its low degree of protonation. 2+ Mg 2+ Ions and coordinated water form coordination bonds, and the formation of a double network structure leads to an increase in strength that exceeds the strength loss caused by the CO2 response. Therefore, compared with the performance of gel particles in deionized water, the gel particles in highly mineralized water show excellent performance of swelling and strength enhancement after CO2 response.

[0019] The present invention also provides the use of the double-network CO2 responsive gel particles for plugging micro-cracks in oil reservoirs.

[0020] Preferably, the application is that at a temperature of 25°C-120°C, the mineralization of the formation water is 0-10%, wherein Ca 2+ Mg 2+ The ion content is 0-1%, and the cracks with a width of 0.2mm-0.5mm in the reservoir are plugged. The double-network CO2 responsive gel particles are evenly dispersed in the formation water and injected into the formation as a plugging agent. The cracks are plugged after aging for 24 hours.

[0021] Preferably, the oil reservoir is a low permeability oil reservoir; further preferably, the oil reservoir is a low permeability oil reservoir subjected to CO2 flooding.

[0022] Beneficial effects of the present invention: 1. In the double-network CO2-responsive gel particles of the present invention, the covalent bonds between acrylamide, zwitterionic monomers, CO2-responsive monomers and crosslinking agents form a first three-dimensional network structure, and the Ca in mineralized water 2+ SO3 in ionic, pyridyl, zwitterionic monomers -and between coordinated water, Mg 2+ There are metal coordination bonds between ions, pyridine groups, carboxyl groups (produced by partial hydrolysis of amide groups) and coordinated water, and the π-π stacking effect between aromatic rings forms a second-layer network structure. The toughness of the double network structure significantly enhances the strength of the gel; the introduction of aromatic ring sulfobetaine zwitterionic monomers with "anti-polyelectrolyte effect" and a large number of water molecules carried by metal coordination bonds increase the strength of the gel particles in highly mineralized water while showing stronger water retention properties.

[0023] 2. The CO2 responsive monomers in the double-network CO2 responsive gel particles provided by the present invention are composed of vinyl pyridine and DMAEMA with different pKa values, wherein the pKa values ​​of 4-vinyl pyridine, 2-vinyl pyridine and DMAEMA are 5.62, 4.98 and 8.18, respectively. After contacting with CO2, DMAEMA with a high pKa value is protonated first, while vinyl pyridine with a low pKa value is not protonated or has a low degree of protonation, so that it can continue to react with Ca in mineralized water. 2+ Mg 2+ As well as coordinating water to form metal coordination bonds, the formation of a double network structure leads to an increase in strength that exceeds the strength loss caused by the CO2 response. Therefore, compared with the performance of gel particles in deionized water, the gel particles in highly mineralized water show excellent performance of swelling and strength enhancement after CO2 response.

[0024] 3. The gel particles of the present invention have the characteristics of swelling and strengthening in highly mineralized water, good CO2 response characteristics, and still have the characteristics of metal coordination cross-linking to enhance gel strength after response, and can effectively seal microcracks during CO2 flooding in highly mineralized microcrack reservoirs. DETAILED DESCRIPTION

[0025] The present invention will be further described below with reference to the embodiments and comparative examples.

[0026] The materials and detection equipment used in each embodiment and comparative example are all existing commonly used commercially available materials and detection equipment, such as acrylamide purchased from Puyang Haizhiyuan Chemical Industry Co., Ltd., 4-vinylpyridine and 2-vinylpyridine were purchased from Jiangsu Bost Chemical Technology Co., Ltd., DMAEMA was purchased from Jinan Century Tongda Chemical Co., Ltd., and other material sources are not described here. Those skilled in the art can select different manufacturers according to their needs.

[0027] The synthesis process of the zwitterionic monomer 4-(2-sulfoethyl)-1-(4-vinylbenzyl)pyridinium betaine is as follows: .

[0028] The specific synthesis steps are as follows: in a 250mL three-necked round-bottom flask equipped with condensation reflux, a thermometer and a magnetic stirrer, 18.72g of 4-pyridineethanesulfonic acid (0.1mol) and 4.0g of NaOH (0.1mol) are dissolved in 150mL of formamide solution, N2 is passed through for 30min, and then 15.26g of p-chloromethylstyrene (0.1mol) is slowly added dropwise. The reaction mixture is stirred at room temperature for 72h. After the reaction is completed, the solid is precipitated in acetone and recovered, and then recrystallized from anhydrous ethanol.

[0029] Synthesis process of zwitterionic monomer 3-(1-(4-vinylbenzyl)-1H-imidazol-3-ium)propane-1-sulfonate: .

[0030] Synthesis process of zwitterionic monomer 3-(dimethyl(4-vinylbenzyl)amino)propanesulfonate: .

[0031] Example 1 A double-network CO2-responsive gel particle, comprising, by mass percentage: 15% acrylamide, 10% zwitterionic monomer, 10% CO2 responsive monomer (the mass ratio of 4-vinylpyridine and DMAEMA is 2:3), 0.3% emulsifier, 0.1% cross-linking agent, 0.1% initiator and the balance water.

[0032] Specifically, in this embodiment, the zwitterionic monomer is 3-(1-(4-vinylbenzyl)-1H-imidazol-3-ium)propane-1-sulfonate, the crosslinking agent is N,N′-methylenebisacrylamide, the initiator is composed of ammonium persulfate and sodium bisulfite in an equal mass ratio, and the water is deionized water.

[0033] The double-network CO2-responsive gel particles provided in this embodiment are prepared by the following method: S1. 15 g of acrylamide, 10 g of 3-(1-(4-vinylbenzyl)-1H-imidazol-3-ium)propane-1-sulfonate, 4 g of 4-vinylpyridine, 6 g of DMAEMA and 0.3 g of emulsifier (0.06 g of sodium dodecyl sulfate + 0.24 g of OP-10) were added to 63.5 g of deionized water, and the mixture was stirred to obtain a first mixed solution; S2. Use 0.1 mol / L NaHCO3 solution to adjust the pH of the first mixed solution to 7.0, 0 ℃ ice bath, into the first mixed solution N2 for a total of 30min, exhaust the air to obtain a second mixed solution; S3. 0.05 g of potassium persulfate and 0.05 g of sodium bisulfite were dissolved in 1 g of deionized water to obtain an initiator solution. The initiator solution was added to the second mixed solution under stirring and continuous N2 flow, followed by addition of 0.1 g of N,N′-methylenebisacrylamide, and the reaction was continued at 40°C and a stirring rate of 200 rpm for 3 h. S4. Cut the reaction product obtained in step S3 into pieces, soak it in anhydrous ethanol for three times, dry it at 60°C for 48h, crush it into particles, and use a sieve to screen the gel particles with an initial particle size of less than 135μm.

[0034] The gel particles are used to seal micro-cracks during CO2 flooding, where the crack width is 0.3 mm.

[0035] Example 2 A double-network CO2 responsive gel particle, which is different from Example 1 in that the zwitterionic monomer is 3-(dimethyl(4-vinylbenzyl)amino)propanesulfonate, and the other components and preparation method are the same as those in Example 1.

[0036] Example 3 A double-network CO2 responsive gel particle, which is different from Example 1 in that the zwitterionic monomer is 4-(2-sulfoethyl)-1-(4-vinylbenzyl)pyridinium betaine, and the other components and preparation method are the same as those in Example 1.

[0037] Example 4 A double-network CO2-responsive gel particle, which is different from Example 1 in that the mass ratio of 4-vinylpyridine to DMAEMA is 1:1, and the other components and preparation method are the same as those in Example 1.

[0038] Example 5 A double-network CO2-responsive gel particle, the mass percentage of each component is as follows: 20% acrylamide, 7.5% 3-(1-(4-vinylbenzyl)-1H-imidazol-3-ium)propane-1-sulfonate, 7.5% mixture of 4-vinylpyridine and DMAEMA, wherein the mass ratio of 4-vinylpyridine to DMAEMA is 2:3, 0.25% N,N′-methylenebisacrylamide, The total mass is 0.075% of ammonium persulfate and sodium bisulfite in equal mass ratios, Residual water; During the preparation process, the feed mass of each component was also replaced accordingly, and the specific preparation method was the same as that in Example 1.

[0039] Example 6 A double-network CO2 responsive gel particle, which is different from Example 1 in that the pyridine monomer is 2-vinylpyridine, and the other components and preparation method are the same as those in Example 1.

[0040] Example 7 A double-network CO2 responsive gel particle, which is different from Example 1 in that the crack width is 0.2 mm, and the other components and preparation method are the same as those of Example 1.

[0041] Example 8 A double-network CO2 responsive gel particle, which is different from Example 1 in that the crack width is 0.5 mm, and the other components and preparation method are the same as those of Example 1.

[0042] Example 9 A double-network CO2 responsive gel particle is used to seal microcracks during CO2 flooding. In this embodiment, the gel particles are selected from the gel particles provided in Example 1.

[0043] The specific application is that at a temperature of 50°C, the mineralization of the formation water is 10%, of which Ca 2+ Mg 2+ The ion content is 1%, and the cracks with a width of 0.3mm are blocked. The double-network CO2 responsive gel particles are evenly dispersed in the mineralized water and injected into the formation as a plugging agent. After aging for 24 hours, the gas string channels are blocked, and the blocking rate of the cracks is ≥90%.

[0044] In this embodiment, the oil reservoir is a low permeability oil reservoir subjected to CO2 flooding.

[0045] Example 10 A double-network CO2 responsive gel particle is used to seal microcracks during CO2 flooding. In this embodiment, the gel particles are selected from the gel particles provided in Example 5.

[0046] The specific application is that at a temperature of 120°C, the mineralization of the formation water is 0.1%, of which Ca 2+ Mg 2+ The ion content is 0.02%, and the cracks with a width of 0.5 mm are blocked. The double-network CO2 responsive gel particles are evenly dispersed in the mineralized water and injected into the formation as a plugging agent. After aging for 24 hours, the gas string channels are blocked, and the blocking rate of the cracks is ≥90%.

[0047] In this embodiment, the oil reservoir is a low permeability oil reservoir subjected to CO2 flooding.

[0048] Embodiment 11 A double-network CO2 responsive gel particle is used to seal microcracks during CO2 flooding. In this embodiment, the gel particles are selected from the gel particles provided in Example 6.

[0049] The specific application is that at a temperature of 85°C, the mineralization of the formation water is 5.5%, of which Ca 2+ Mg 2+ The ion content is 0.4%, and the cracks with a width of 0.2mm are blocked. The double-network CO2 responsive gel particles are evenly dispersed in the mineralized water and injected into the formation as a plugging agent. After aging for 24 hours, the gas string channels are blocked, and the blocking rate of the cracks is ≥90%.

[0050] In this embodiment, the oil reservoir is a low permeability oil reservoir subjected to CO2 flooding.

[0051] Comparative Example 1 A CO2 responsive gel particle, which is different from Example 1 in that the mass proportion of N,N′-methylenebisacrylamide is 0.025%; the feed mass of each component in the preparation process is also replaced accordingly, and the specific preparation method is the same as Example 1.

[0052] Comparative Example 2 A CO2-responsive gel particle, which is different from Example 1 in that the amount of initiator used is 0.2%, the mass ratio of sodium bisulfite to ammonium persulfate is 1:1, and the feed mass of each component in the preparation process is also replaced accordingly. The specific preparation method is the same as that in Example 1.

[0053] Comparative Example 3 A CO2 responsive gel particle, which is different from Example 1 in that sulfobetaine methacrylate (SBMA) is used as the zwitterionic monomer; other components and preparation methods are the same as those in Example 1.

[0054] Comparative Example 4 A CO2 responsive gel particle, which is different from Example 1 in that the CO2 responsive monomer is a single 4-vinylpyridine; other components and preparation methods are the same as those in Example 1.

[0055] Comparative Example 5 A CO2 responsive gel particle, which is different from Example 1 in that the CO2 responsive monomer is a single DMAEMA; other components and preparation methods are the same as those in Example 1.

[0056] Comparative Example 6 A CO2 responsive gel particle, which is different from Example 1 in that the mass proportion of the CO2 responsive monomer is 1% (the mass ratio of 4-vinylpyridine and DMAEMA is 2:3), the feed mass of each component in the preparation process is also replaced accordingly, and the specific preparation method is the same as Example 1.

[0057] Experimental Example 1: 1). Expansion test a. Neutral environment Will have the same quality M The dried gel particles of 0 were placed in beakers filled with deionized water and formation water respectively, and expanded in a 60℃ high-temperature forced air drying oven for 24 hours until the gel particles reached water saturation. The gel particles were then wiped with filter paper and the mass of the swollen gel particles was weighed. M 1. Calculate the expansion multiple of gel particles in neutral environment according to the following formula: SR Among them, the total mineralization of formation water is 10%, Ca 2+ Mg 2+ The ion content is 1%.

[0058] (I) In formula (I), SR is the expansion multiple, dimensionless; M 0 is the mass of the gel particles before swelling, in g; M 1 is the mass of the swollen gel particles, in g.

[0059] b.CO2 environment Will have the same quality M The dried gel particles with a concentration of 0 were placed in a high-temperature and high-pressure reactor filled with mineralized water, CO2 was introduced into the reactor to a pressure of about 4MPa, and then the reactor was placed in a high-temperature forced air drying oven at 60°C for expansion for 24 hours, after which the mass was taken out and measured. The expansion multiple of the gel particles in mineralized water under the CO2 environment was calculated according to the above formula.

[0060] By comparing the experimental data under neutral and CO2 environments, the CO2 response characteristics of the gel particles were observed; by comparing the expansion multiples of the gel particles in deionized water and mineralized water, it was analyzed whether the gel particles had anti-polyelectrolyte properties.

[0061] 2). Gel strength test The elastic modulus of the gel particles after 24 h of swelling under different conditions was measured using the plate measurement system in the Anton Paar rheometer to analyze whether the gel particles showed strength enhancement behavior in mineralized water. The shear strain in the experiment was 1% and the oscillation frequency was 0.1-100 Hz.

[0062] 3). Plugging performance test The sealing ability of gel particles was evaluated by a physical model with a length of 10 cm, a diameter of 2.5 cm, fracture widths of 0.2 mm, 0.3 mm, and 0.5 mm, respectively, and a matrix permeability of 45 mD. The gel particle system was tested in the above formation water (i.e., the total mineralization was 10%, of which Ca 2+ Mg 2+ After dispersion in water (with ion content of 1%), the concentration is 5000 mg·L -1 , the specific experimental steps are: ①Evacuate the core and calculate the porosity of the core; ② Connect the pipelines, assemble the experimental device, set the constant temperature of the oven to 60°C, the confining pressure to 8 MPa, and the back pressure to 4 MPa; ③Inject CO2 until the pressure is stable and record the pressure difference after stabilization P 1; ④ Inject 0.6PV of gel particle suspension and record the pressure changes during the injection process. ⑤After aging at 60℃ for 24 hours, continue to inject CO2 gas until the pressure stabilizes. The final pressure difference is P 2; ⑥Through blocking rate F Evaluate the sealing performance of the gel system. (II) In formula (II), F is the blocking rate, unit is %; P 1 is the initial pressure difference stable value, in MPa; P 2 is the final pressure difference stable value, in MPa.

[0063] The test results are shown in the following table: Table 1 Test results of examples and comparative examples

[0064] In Table 1, the expansion multiple is a dimensionless parameter, and the unit of strength is Pa. The plugging rates of Examples 1 to 6 and Comparative Examples 1 to 6 are measured in a physical model with a crack width of 0.3 mm, and the plugging rates of Examples 7 and 8 are measured in physical models with crack widths of 0.2 mm and 0.5 mm, respectively.

[0065] From the data in Table 1, it can be seen that the expansion multiple and storage modulus of the gel particles prepared in Example 1 in deionized water under neutral conditions are 30.8 and 1548 Pa, respectively, while the corresponding results in mineralized water are 34.4 and 2142 Pa. Compared with the gel particles in deionized water, the gel particles in highly mineralized water have higher strength and stronger water retention performance. This is because there is only a single-layer network structure formed between the monomer and the crosslinking agent MBA in deionized water, while the Ca in mineralized water 2+ SO in ionic, pyridyl, and zwitterionic monomers 3- and between coordinated water, and, Mg in mineralized water 2+ Metal coordination bonds can be formed between ions, pyridine groups, carboxyl groups (produced by partial hydrolysis of amide groups) and coordinated water. At the same time, there are a large number of π-π stacking effects between zwitterions and pyridines, which can cooperate with the network between monomers and crosslinkers to build a double network structure, thereby significantly enhancing the strength of the gel particles. On the other hand, the introduction of zwitterionic monomers allows electrostatic attraction between polymer chain segments, so the network structure formed by gel particles in deionized water is relatively dense; in mineralized water, the destruction of ionic bonds in the network and the osmotic pressure difference make the polymer chain segments in an extended state, and more water molecules are loaded in the network structure. At the same time, metal ions can carry a large number of water molecules through coordination bonds to participate in the reconstruction of the multiphase structure of the gel, so that the gel particles have stronger water retention properties in mineralized water.

[0066] After CO2 was introduced into the mineralized water, the CO2-responsive monomers in the gel particles were protonated, the electrostatic repulsion between the polymer chains increased, the gel particles swelled significantly, and the expansion multiple increased to 48.5. At the same time, it can be seen that the strength of the gel particles in the mineralized water after CO2 response is 1806Pa, which is still significantly higher than the strength in deionized water in a neutral environment. This is because the gel particles introduced two CO2-responsive monomers, vinylpyridine and DMAEMA, of which 4-vinylpyridine has a pKa of 5.62 and DMAEMA has a pKa of 8.18. After CO2 was introduced, DMAEMA with a high pKa value was protonated first, increasing the expansion multiple of the gel particles. Vinylpyridine with a low degree of protonation can still react with Ca in the mineralized water. 2+ Mg 2+ As well as coordinated water, a three-dimensional network structure is formed under the action of a large number of π-π bonds between aromatic rings. When the gel strength enhanced by the formation of the second layer of network structure exceeds the strength loss caused by expansion, the overall mechanical properties of the gel will be improved, so that the gel particles can maintain structural strength while the expansion multiple is significantly increased during CO2 flooding in high-mineralization reservoirs.

[0067] When the temperature is 60℃, the salt content in mineralized water is 10%, including Ca 2+When CO2 flooding was carried out in a core with an ion concentration of 1% and a crack width of 0.3 mm, the plugging rate of the gel particles was 99.0%, which indicates that the double-network CO2 responsive gel particles provided by the present invention have excellent plugging ability for microcracks during CO2 flooding in a high-salt environment.

[0068] Compared with Example 1, the expansion multiple, storage modulus and plugging performance of the gel particles in Example 2 are slightly reduced. Compared with 3-(1-(4-vinylbenzyl)-1H-imidazol-3-ium)propane-1-sulfonate, the 3-(dimethyl(4-vinylbenzyl)amino)propanesulfonate chain lacks a benzene ring with a rigid structure, which reduces the strength of the gel particles. At the same time, the hydration ability of 3-(dimethyl(4-vinylbenzyl)amino)propanesulfonate is weak, which slightly reduces the expansion multiple of the gel, and thus the plugging rate decreases.

[0069] Compared with Example 1, the zwitterionic monomer in Example 3 is 4-(2-sulfoethyl)-1-(4-vinylbenzyl)pyridinium betaine. Due to the different hydration abilities of the two monomers, the expansion multiple and the plugging effect of the gel particles in Example 3 are slightly reduced.

[0070] Compared with Example 1, in Example 4, the mass ratio of vinylpyridine to dimethylaminoethyl methacrylate is 1:1, the mass fraction of vinylpyridine increases, and the enhanced coordination effect increases the strength of the gel particles in the mineralized water. At the same time, the mass proportion of DMAEMA decreases, and the CO2 response characteristics of the gel particles decrease. Therefore, the expansion multiple and the blocking effect of the gel particles are reduced.

[0071] Compared with Example 1, the concentrations of acrylamide and cross-linking agent in Example 5 are significantly increased, the intermolecular cross-linking density is increased, a dense network structure is formed, and the elastic modulus is significantly increased. However, the significant increase in the cross-linking density leads to a decrease in the free space inside the particles and a decrease in the expansion multiple of the gel particles. At the same time, the reduction in the mass proportion of zwitterionic monomers and CO2 responsive monomers reduces the CO2 responsiveness, anti-polyelectrolyte effect and metal coordination ability of the gel particles, and the blocking performance is reduced.

[0072] Compared with Example 1, the pyridine monomer in Example 6 is 2-vinylpyridine, which has a slightly lower solubility in deionized water than 4-vinylpyridine, and therefore the expansion multiple in deionized water is smaller than that in Example 1; at the same time, the pKa value of 2-vinylpyridine is lower than that of 4-vinylpyridine, and therefore its protonation degree in a CO2 environment is low. Therefore, compared with Example 1, the expansion multiple of the gel particles after the CO2 response in mineralized water is reduced, the strength is increased, and the plugging performance is slightly decreased.

[0073] The crack width of the physical model in Example 1 is 0.3 mm, while the crack widths of the physical models in Examples 7 and 8 are 0.2 mm and 0.5 mm, respectively. When the crack width is 0.3 mm, the gel particles have a good match with the crack width, so it has a good plugging effect; when the crack width is 0.2 mm, the crack width may be smaller than the average particle size of the particles, so the gel particles are mainly concentrated in the middle and front end of the crack core, and the plugging performance is slightly reduced; when the crack width is 0.5 mm, the crack width may be larger than the average particle size of the particles. Although the particles can completely enter the crack and the injection performance is good, the plugging effect is reduced.

[0074] Compared with Example 1, the mass fraction of the crosslinking agent MBA in Comparative Example 1 is 0.025%. At this time, the crosslinking agent concentration is too low, the degree of crosslinking is incomplete, and a complete three-dimensional network structure cannot be formed. Some gel particles are dissolved in water, and the gel strength is significantly reduced. After CO2 response, the gel network structure is almost completely destroyed, and the plugging rate is only 33.3%.

[0075] Compared with Example 1, the mass fraction of the initiator in Comparative Example 2 is 0.2%, wherein the mass ratio of sodium bisulfite to ammonium persulfate is 1:1. At this time, the amount of initiator used is too large, the initiation rate increases too quickly, the reaction heat in the system is not easy to dissipate, resulting in shorter polymer molecular chains, which ultimately leads to a decrease in the expansion multiple and elastic modulus of the gel particles.

[0076] Compared with Example 1, the zwitterionic monomer in Comparative Example 3 is SBMA, which has excellent hydrophilicity, and therefore has stronger water absorption performance in deionized water, with an expansion multiple of 33.1. However, it is precisely because of its excellent hydrophilicity that its ion responsiveness is greatly weakened, and no anti-polyelectrolyte effect occurs in mineralized water, and the water retention performance is even slightly reduced. The introduction of the benzene ring and imidazole structure in the zwitterionic monomer of Example 1 increases the hydrophobicity of the monomer on the one hand, and enhances the binding energy between zwitterions on the other hand, so that the gel particles generate a relatively dense and compact electrostatic cross-linked network in deionized water, which provides sufficient space for the subsequent swelling of the gel particles in mineralized water. Therefore, after the gel particles are dispersed in mineralized water, the free counterions in the mineralized water penetrate into the polymer chain, and the stronger binding energy between the counterions and the zwitterions destroys the dipole action within the polymer chain / between the chains, resulting in the polymer chain segment conformation in the salt water being in an extended state. Therefore, compared with Comparative Example 3, the gel particles in Example 1 have an obvious anti-polyelectrolyte effect in brine, thereby improving its ability to plug microcracks during CO2 flooding in highly mineralized oil reservoirs.

[0077] Compared with Example 1, the CO2 responsive monomer in Comparative Example 4 is only 4-vinylpyridine, and its lower pKa value makes it less responsive to CO2, so the expansion multiple after CO2 response does not increase significantly, and the plugging performance is reduced.

[0078] Compared with Example 1, the CO2 responsive monomer in Comparative Example 5 is only DMAEMA, and its sensitivity to CO2 response significantly increases the expansion multiple of the gel particles after the response. However, the absence of pyridine groups results in almost no formation of metal coordination bonds in the gel particles. Therefore, the storage modulus of the gel particles after expansion is significantly reduced. The presence of divalent metal ions in mineralized water further deteriorates the strength and blocking effect of the gel particles.

[0079] Compared with Example 1, the mass fraction of the CO2 response monomer in Comparative Example 6 is 1%. The reduction in the mass fraction of the response monomer weakens the CO2 responsiveness of the gel particles, and at the same time reduces the coordination ability between pyridine and other ions. Therefore, when CO2 flooding is carried out in high-mineralization formations, the strength and sealing performance of the gel particles are not ideal.

Claims

1. A double-network CO2-responsive gel particle, characterized in that: Prepared by the following method: S1. Add acrylamide, zwitterionic monomer, CO2 responsive monomer and emulsifier into deionized water, stir and mix to obtain a first mixed solution; S2. The pH of the first mixed solution was adjusted to 7, and N2 was introduced into the first mixed solution under an ice bath to exhaust the air to obtain a second mixed solution; S3. The initiator and the cross-linking agent were successively added to the second mixed solution under stirring, the temperature was adjusted to 30 ℃ -60 ℃ and kept passing N2, and the reaction was carried out for 2h-4h to obtain a reaction product; S4. The reaction product obtained in step S3 is washed with anhydrous ethanol, dried, ground and sieved to obtain the target product, double-network CO2-responsive gel particles; In the preparation method, the percentage of each component is: 15%-20% acrylamide, 5-10% zwitterionic monomer, 5-10% CO2 responsive monomer, 0.25-1% emulsifier, 0.05%-0.25% crosslinker, 0.075%-0.15% initiator and the balance water. The CO2 response monomer is composed of vinyl pyridine and N,N-dimethylaminoethyl methacrylate in a mass ratio of (0.5-1):1; The zwitterionic monomer is selected from 4-(2-sulfoethyl)-1-(4-vinylbenzyl)pyridinium betaine, 3-(1-(4-vinylbenzyl)-1H-imidazol-3-ium)propane-1-sulfonate or 3-(dimethyl(4-vinylbenzyl)amino)propanesulfonate.

2. The double-network CO2-responsive gel particle according to claim 1, characterized in that: The vinyl pyridine is selected from one of 4-vinyl pyridine and 2-vinyl pyridine.

3. The double-network CO2-responsive gel particle according to claim 2, characterized in that: The mass ratio of vinyl pyridine to N,N-dimethylaminoethyl methacrylate is 2:

3.

4. The double-network CO2-responsive gel particle according to claim 1, characterized in that: The emulsifier is one or two of sodium dodecyl sulfate, OP-10 or sodium stearate; The cross-linking agent is selected from one of N,N′-methylenebisacrylamide and polyethylene glycol diacrylate or a mixture of the two; The initiator is selected from azo compound 2,2'-azo[2-(2-imidazoline-2-yl)propane] dihydrochloride, or the initiator is composed of sodium bisulfite and ammonium persulfate.

5. The double-network CO2-responsive gel particle according to claim 4, characterized in that: The emulsifier is a mixture of sodium dodecyl sulfate and OP-10, with a mass ratio of 1:4; The crosslinking agent is selected from N,N′-methylenebisacrylamide and polyethylene glycol diacrylate, and the mass ratio of the two is (1.5-6):1; The initiator consists of sodium bisulfite and ammonium persulfate, and the molar ratio of sodium bisulfite to ammonium persulfate is in the range of (0.6-1.2):

1.

6. The double-network CO2-responsive gel particle according to claim 1, characterized in that: In step S2, the ice bath temperature is 0°C; In step S3, the stirring speed is 100 rpm-500 rpm; In step S4, the drying temperature is 60° C., the drying time is 48 h, and the particles with an initial particle size of less than 135 μm are screened using a sieve.

7. The double-network CO2-responsive gel particle according to claim 1, characterized in that: In the preparation method, the mass percentage of each component is: 15% acrylamide, 10% zwitterionic monomer, 10% CO2 responsive monomer, 0.3% emulsifier, 0.1% cross-linking agent, 0.1% initiator and balance water, wherein the CO2 responsive monomer is composed of 4-vinylpyridine and N,N-dimethylaminoethyl methacrylate in a mass ratio of 2:

3.

8. Use of the double-network CO2 responsive gel particles as described in any one of claims 1 to 7 to plug micro-cracks in oil reservoirs.

9. The use according to claim 8, characterized in that The specific application is that at a temperature of 25℃-120℃, the mineralization of the formation water is 0-10%, and the Ca 2+ Mg 2+ The ion content is 0-1%, and the cracks with a width of 0.2mm-0.5mm in the reservoir are plugged. The double-network CO2 responsive gel particles are evenly dispersed in the formation water and injected into the formation as a plugging agent. The cracks are plugged after aging for 24 hours.

10. The use according to claim 8, characterized in that The oil reservoir is a low permeability oil reservoir for CO2 flooding.

Citation Information

Patent Citations

  • Preparation method of temperature and CO2 double-responsive block copolymer nano micelle

    CN103881040A

  • Responsive interpenetrating network gel particles for preventing CO2 gas channeling of compact oil reservoirs and preparation method thereof

    CN111548465A

  • CO2 response type salt-tolerant polymer gel particle and application thereof

    CN118324986A

  • Acid gas intelligent response gel material as well as preparation method and application thereof

    CN118580421A

  • CO2 response type gel particle and preparation method thereof

    CN118878742A

Cited By

  • Temperature-resistant and salt-resistant in-situ plugging reinforced gel composition, gel and preparation method and application thereof

    CN120535692A

  • Temperature and salt resistant in situ plugging enhanced gel composition, gels, and methods of making and using the same

    CN120535692B

  • Temperature-resistant and salt-tolerant in-situ plugging enhanced gel compositions, gels, preparation methods and applications

    US12624275B1